The Effect of Implementing the Kaizen Philosophy on Employee Performance Through Employee Innovation and Work Efficiency: A Case Study at XYZ Bank in West Kalimantan - Sinta, Sinta; Krisprimandoyo , Denpharanto Agung; Santoso , William (Journal Research of Social Science, Economics, and Management, 2026)
The banking industry has experienced increasingly intense competition, forcing companies to continuously improve service quality and operational efficiency through enhanced employee performance. This study investigated the effect of implementing the Kaizen philosophy on employee performance, with particular attention to the mediating role of employee innovation and work efficiency at PT XYZ in the West Kalimantan region. The Resource-Based View (RBV) framework provided the theoretical foundation for this research. A quantitative research design was employed, with data collected through questionnaires administered to 100 employees of PT XYZ in West Kalimantan, selected using purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.0.3 to examine both direct and indirect relationships among variables. The results revealed that the implementation of the Kaizen philosophy did not have a significant direct effect on employee performance. However, it had a positive and significant effect on both employee innovation and work efficiency. Furthermore, work efficiency had a positive and significant effect on employee performance and served as a full mediator in the relationship between Kaizen implementation and employee performance. In contrast, employee innovation did not significantly affect employee performance and did not function as a mediating variable. These findings indicate that, in the banking industry, the implementation of the Kaizen philosophy is more effective in improving employee performance through work efficiency rather than through employee innovation.